Speed vs. Thought: Epistemological and educational challenges of the automation and AI civilization - Dominici, Piero; Versuti, Andrea (Revista Comunicação Midiática, 2026)
Contemporary society, immersed in the digital revolution, faces hyper-speed information that limits critical reflection and exacerbates social vulnerabilities. The analysis identifies the "ultimate error”: the attempt to manage complex systems using linear logic, sustained by the tyranny of concreteness and the illusion of technological control. This mindset fuels practices such as algorithmic surveillance and surveillance capitalism, which progressively erode civil liberties and individual autonomy. As a cultural and strategic response, a "new humanism" is proposed that revalues the human factor and systemic ethics. This humanism focuses on the ability to "inhabit complexity," integrating error and emergence as essential heuristic resources for adaptation. Education emerges as a strategic axis, privileging knowing-how-to-be and knowing-how-to-act, forming citizens capable of coping with uncertainty and resisting the logic of hypervelocity.